Bullying and social functioning, schemas, and beliefs among youth at clinical high risk for psychosis. Issue 3 (2nd May 2021) - Braun, Amy; Santesteban‐Echarri, Olga; Cadenhead, Kristin S.; Cornblatt, Barbara A.; Granholm, Eric; Addington, Jean
Abstract: Background: Individuals at clinical high‐risk (CHR) for psychosis experience high rates of bullying. There is little research on the differences between CHR who did and did not experience bullying. However, there is evidence that bullying may be related to negative schemas and social impairment. Objectives: To examine differences in core schemas, asocial and defeatist beliefs, and social functioning between those who did and did not report bullying experiences in a large sample of CHR individuals. We hypothesized that bullying in CHR youth would be associated with poorer social functioning, increased maladaptive beliefs, and negative core schemas. Methods: CHR participants ( N = 203) were split into those who did and did not report experiencing bullying. The two groups were compared on demographic characteristics, social functioning, and belief variables, using the Brief Core Schemas Scale, the Asocial Beliefs Scale, the Defeatist Performance Attitudes Scale, and the First Episode Social Functioning Scale. Results: 72.9% reported experiencing bullying. These participants had greater severity of negative schemas about others and asocial and defeatist performance beliefs, and lower social functioning scores. Conclusions: Prevalence of bullying among CHR participants is high. Bullying may be a risk factor for increased asocial and defeatist beliefs, negative core schemas, and poor social functioning. Targeting maladaptive schemas and beliefs during treatment may serve to improve functional outcomes in this group.